Criminological Aspects of Border Crime (Archives of Criminology, 2002)
In this study the author indicates the main problems that appeared in Poland as a result of the opening of borders after the transition to a new economic and political system launched in 1989. The list is headed by offenses committed by foreign nationals, smuggling activities, illegal crossing of frontiers, and  population movements, especially from very low-income countries.      Border crime is defined here as both illegal border crossing, customs and currency offenses, forgery of documents and crime againts institutions. Border crime can be examined in a large numer of aspects as offenses which ere a threat to fundamental public policy interests. The crux of the matter lies in the motives and aims of the perpetrator.      When we refer to border crime we have in mind the kind of offenses that are associated with cross-border movement of persons and objects involved in an illegal activity The commission of offenses falling into this category is not confined solely to border regions. The area of operations of criminals of this kind may be the whole of a country. Border crime is crime of a special kind. Its effects and in particular its further consequences are not always visible. Nor in all such cases is there an injured party, though it should be noted that serious harm may be suffered by people smuggled across borders and that injury is caused to victims of smuggling-related car theft.      It is worth drawing attention to the etiology of this kind of crime. Among the internal influences contributing to its growth should be included the closure or collapse of workplaces, state farms and industrial enterprises, especially along Poland’s eastern border, and the consequent rise in unemployment. In recent years there has been a notable decline in the public’s standard of living, which has prompted some of them to seek alternative or additional sources of income.With increasing frequency people set their sights on swift multiplication of wealth and see in smuggling, for instance, a relatively simple and low-risk way of making money. It is worth noting  a judicial tendency towards unduly lenient treatment of perperators of border crime and to hand down light sentences (most glaringly, for organizacion of illegal border crossing). Another development has been a steep rise in the incidence of pathological phenomena among officials, such as forgery or falsification of documents, bribery or entry into the structures of criminal groups.       Much more dangerous are the external factors driving border crime, such as steadily worsening economic decline in parts o fthe Middle East, Asia and the former Soviet Union and  rising unemployment and inflation in the countries concerned. Other causes are wars, national, ethnic and religious conflicts and the inadequacy of the technical protection of frontiers. Not without significance is the continuing demand in the East for cars of Western make and the possibility of legalizing their acquisition if they have been stolen. There has also been an intensification of corrupt practices among public officials with an influence on the state of national security and inviolability of frontiers (especially among the border guard forces in Belarus and Ukraine). Also conducive to the growth of crime is the further organization and specialization of criminal groups pursuing activities on both sides of the frontier.       The author also offers a detailed picture of selected types of border crime. Her study centers on the legal and criminological aspects of the crime of illegal entry. She indicates the methods of committing this crime employed by its perpetrators at both border crossings and along smuggling routes. She depicts the mechanisms involved in the smuggling of persons with particular emphasis on the role played in such trafficking by organized criminal groups.       Another criminal activity worth attention is smuggling, chiefly of liquor, cigarettes, cars, drugs, animals, guns, etc. This crime is a threat to the economic interests of the state which incurs  significant losses of revenue in this respect.  The author brings out the complex, underground modus operandi of the criminals involved and stresses the prominence in this illicit activity of organized criminal groups.       The data illustrating border crime points to the continued persistence of threats from illegal immigration into Poland, including in many cases in organized forms, and its  transformation from a transit to a destination country. Because of the unabating demand in the former Soviet republics for Western cars rhe organizers of smuggling rings will probably develop more sophisticated methods of falsifying the documents of cars (mostly luxury models) stolen in West-European countries. As at present there will be continued smuggling, both by individuals and in organized forms (of considerable value per consignment), of liquor into Poland and of cigarettes bound for Poland and Germany. Intensification of attempts to corrupt the personnel (including senior officers) of watchtowers and border crossings.       The most important role in prevention and  suppression of border crime is played by Border Guard personnel. More and more often they are equipped with modern equipment for X-raying baggage and carry out passport checks by means of readers connected to a computer database.  Border Guard personel also engage in operations outside the border zone and conduct searches of dwellings and premises belonging to the organizers of illegal cross-border traffic. Not infrequently they face an increased element of risk. Criminals often possess firearms, gas and other dangerous implements. Hence the importance of specialist  training, physical fitness, unarmed combat skills and the ability to handle weapons.       An important erement in fighting border crime is cooperation with other public institutions. Preventive action and operational, surveillance and investigative measures aimed at improving the state of security and public order and detection and expulsion of foreign nationals who have entered Poland  illegally are carried out in the border zone in collaboration with the police.                   Because of the nature or its responsibilities and the international connections of criminal groups the Border Guard maintains day-to-day liaison with its counterparts in  other countries. Among the most important areas of cooperation between the border authorities of European Union members, Central and East European countries, the United States and Canada are interchange of information about tasks, structures, jurisdictions, powers and problems relating to cross-border traffic and border crime and interaction in operational and investigative activities. There is a particularly successful record  of cooperarion with the German authorities (specifically the BGS).       It is worth stressing that amendmends to the Border Guard Act adopted in 2001 provide for its equipment with additional powers for combating corruption, including operational oversight, „sting” operations, the offering or acceptance of bribes, and imposes on Border Guard personnel and employees the requirement to file declarations of assets. The powers in question could be a significant boost to the prevention and suppression of border crime.